Reproductive strategy and gamete development of an invasive fanworm, Sabella spallanzanii (Polychaeta: Sabellidae), a field study in Gulf St Vincent, South Australia. - Aria L Lee; Katherine A Dafforn; Pat A Hutchings; Emma L Johnston (PLoS ONE)
Several reproductive strategies have been identified as key factors that contribute to the establishment and dispersal of invasive species in new environments. These strategies include early maturity, high reproductive capacity and flexibility in timing of reproduction. It is therefore critical to investigate the reproductive biology of target exotic species to understand their potential for population increase and invasive spread, and to inform management control strategies. The European fanworm, Sabella spallanzanii (Gmelin 1791), has established invasive populations along the southern coast of Australia. Gamete development and reproductive periodicity of this worm were investigated in two populations in Gulf St Vincent in South Australia over a 1 year period (July 2012 to June 2013). Samples of worms were collected monthly and dissected for histological analysis. Most individuals reached reproductive maturity at 70 mm body length (thorax and abdomen). Individuals from both populations contained mature and developing gametes year-round and a distinct spawning season was not observed. This may indicate sustained spawning by the population over the year, which provides a constant supply of new recruits to the area. Body length and egg size of worms from these populations were smaller than conspecifics in its native range and other invasive locations. Reproduction and development of S. spallanzanii differs not only between native and invasive locations, but also within invasive locations. This study has shown that S. spallanzanii exhibits a higher phenotypic plasticity and reproductive flexibility than previously known.